Assessment of Carcinogenic and Non-Carcinogenic Health Risks from Heavy and trace metals in Groundwater Wells in Sabha City - Saeda Maatoq; Ebtesam Altaher; Masauda Alshatory; Aisha Alshanoukie (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to evaluate the non-carcinogenic and carcinogenic health risks associated with heavy and trace metals (HMs and TMs) in groundwater wells in Sabha City, Libya. Thirty-six samples were collected from nine wells, coded S1–S9. The results showed that the concentrations of Ni, Mn, Zn, Cr, and Cu were within the permissible limits established by the USEPA and WHO. In contrast, Fe concentrations exceeded the permissible limit in wells S2, S3, S7, S8, and S9, with average concentrations of 3.502, 1.210, .410, .405, and 1.948 mg/L, respectively. Pb concentrations exceeded the WHO permissible limit in samples S1, S2, S6, S7, S8, and S9, with average values of .0437, .0362, .0302, .0590, .0242, and .0200 mg/L, respectively. Cd concentrations exceeded the permissible limit in samples S2, S3, S4, S5, S6, S7, S8, and S9, with average concentrations of .0055, .0157, .0230, .0088, .0058, .0045, .0150, and .0150 mg/L, respectively. Mathematical models were used to calculate the Average Daily Dose (ADD). The results indicated that the ADD values for HMs and TMs through ingestion and dermal exposure pathways for both adults and children were within the acceptable limits. The Total Hazard Quotient (THQ) and Hazard Index (HI) values for all detected metals were less than 1, indicating no significant non-carcinogenic health risks to adults or children. However, the Target Cancer Risk (TCR) values ranged from low to moderate carcinogenic risk levels. The sources of metals in groundwater were evaluated using correlation analysis, Principal Component Analysis (PCA), and Cluster Analysis (CA). The results revealed strong correlations among the studied metals, suggesting that they originate from common sources and follow similar geochemical pathways.